Analisis Pengendalian Persediaan Bahan Baku Utama Tangki Air Menggunakan Metode Continuous Review System (CRS) pada PT. XYZ - Waaidzin, Zubaidu; Mundari, Siti (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
PT XYZ is a manufacturing company headquartered in Surabaya that produces plastic‑based products, particularly water storage tanks. PT BIS occasionally encounters both excess raw‑material inventory (overstock) and shortages (stockouts) of its primary tank materials namely first‑layer and second‑layer plastic pellets while in certain months the third‑layer pellets accumulate in surplus. To resolve these issues, the company applied the CRS method to optimize raw‑material inventory levels, preventing stockouts and ensuring real‑time fulfillment of product demand. Using CRS, the optimal purchase quantities were determined to be 7.002 kg for layer 1, 6.398 kg for layer 2, and 5.453 kg for layer 3, at a total cost of IDR 25.266.957 down from the previous cost of IDR 29.997.842. By incorporating safety stock and reorder‑point calculations, the CRS method prevented stockouts and reduced inventory expenses by approximately IDR 4.731.000.